"Sandwich" wound dressing to reduce surgical site infections during sacrococcygeal surgery: A retrospective analysis. Issue 2 (May 2021) - Xu, Sirui; Li, Song; Yan, Fei; Han, Shuang; Lin, Shan; Gu, Jiaao; Yu, Zhange; Shao, Tuo
Abstract: Objective: To explore whether the "sandwich" wound dressing method with a hydrocolloid dressing can effectively reduce surgical site infection rates in sacrococcygeal aseptic operations. Methods: A retrospective cohort of patients with sacrococcygeal aseptic operations (class I incision category) from January 2017 to March 2018 were divided into intervention (sandwich dressing) and control groups (conventional dressing). The surgical site infections (SSI) rate, wound healing course, hospitalization time, and medical costs in the two groups were determined. To exclude the influence of other factors, operation time, blood loss, age, sex ratio, the distance of the incision from the distal edge to the anus, and initial defecation times were compared between the groups. Results: The SSI rates and medical costs in the interventional group were significantly lower than the control group (0% vs 78.57%, P < 0.0001; 3.27 ± 0.98 vs 5.83 ± 1.66 ¥10, 000, p < 0.0001). Hospitalization times were also lower in the intervention compared to the control group (17.05 ± 4.77 vs 34.50 ± 15.47 day, P = 0.001). Conclusions: The sandwich wound dressing method with a hydrocolloid dressing can effectively prevent SSI during sacrococcygeal aseptic surgery. Highlights: The incidence of surgical site infection (SSI) was relatively high in sacrococcygeal aseptic operations. A novel "Sandwich" dressing method with hydrocolloid dressing could significantly reduce the incidence of SSI. New dressing method further reduced hospitalization times and total medical costs.